Islam sebagai "al-Din": beberapa pengamatan terhadap pemikiran Syed Muhammad Naquib al-Attas - Abdul Rani, Mohd Zariat (Department of 'Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya, 2003)
Syed Muhammad Naquib al-Attas has drawn the attention of the Muslims to their dilemma in their own misunderstandings and misperceptions of Islam. In his exposition on the concept of religion, al-Attas examined four significant concepts derived from the word "al-Din," which are in debtedness, natural tendency or inclination, judicious power and submissiveness. He indeed proposed all of these concepts as a major foundation of a Muslim's life. In line with these concepts explained by al-Attas, the meaning of the "Nature of Man" in which he clarified the reality of man's existence and his role as Allah creation. Furthermore, in his explanation on meaning of the "Nature of Knowledge," al-Attas elaborated the classification of knowledge that must be understood by Muslims. Along with the arguments, he also redefined the meaning of progression, development and change to cohere with the spirit of Islam. Precisely, al-Attas elaborated most of his arguments based on concrete understanding of Islamic "Vision of Reality" and the foundation of ethics and morality, which to him are perfect guides to every Muslims' life. Taking into consideration of al-Attas's ideas, this paper will look into his concepts of Islam as "al-Din" (a way of life) and highlight his clarifications on the concept of the "Nature of Man" and the "Nature of Knowledge."